Review of Prescription Writing in Veterinary Medicine - Sadaat, Syed Sher Shah (Journal of Natural Sciences – Kabul University, 2022)
Prescription writing in veterinary medicine, similar to human medicine, is a legally recognized document issued by licensed veterinarians, physicians, or dentists. A prescription instructs a pharmacist to prepare the prescribed medicine, affix usage directions, and dispense it to the client or patient. In veterinary medicine, dispensing involves the preparation and distribution of medicine for use by animal patients. Veterinarians must adhere to legal requirements and ensure prescriptions are accurate and error-free. Essential elements such as date, owner details, species, identification, abbreviations, and clear directions must be included and correctly formatted.